Kolmogorov widths of the Nikol’skii – Besov classes of periodic functions of many variables in the space of quasi-continuous functions - Romanyuk , A. S.; Yanchenko, S. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 2022)
UDC 517.51 We obtain the order estimates of M-dimensional Kolmogorov width for the Nikol’skii – Besov classes with dominating mixed derivative of periodic functions of many variables in the metric of the space of quasi-continuous functions (QC-space).